Genetic algorithm approach to asymmetric capacitated vehicle routing: A case study on bread distribution in Istanbul, Turkiye - Meniz, Busra; Tiryaki, Fatma (GROWING SCIENCE, 2024)
Conveying the products to the customers under optimized circumstances is as crucial for the companies as the production itself. One optimization strategy to consider is transportation with the minimum quantity of vehicles and the selection of courses with the minimum distance between the locations. In other words, it is the examination of the solution to the Vehicle Routing Problem (VRP), particularly the Capacitated VRP (CVRP), which is a more realistic modelization approach. For businesses that perform distribution to customers frequently, such as management work with the coordination of daily distribution, finishing the distribution on time is of great importance. In big cities with complicated roads and many dropping points, this can be achieved by benefiting from the systematic modeling of the CVRP. In this study, the delivery network investigation for one production facility of the Istanbul People's Bread positioned on the Asian side of Istanbul, Turkiye that distributes three times a day will be the focus of interest. The corresponding Asymmetric CVRP (ACVRP) for the facility network and 215 bread-selling buffets with authentic driving distances will be solved with the Genetic Algorithm (GA), and an optimized transportation network will be presented. (c) 2024 by the authors; licensee Growing Science, Canada.
Keywords: Genetic algorithm; People's bread; Asymmetric capacitated vehicle routing; Optimization; Sustainability; NETWORK; Operations Research & Management Science